The performance on learning tasks of patients in the early stages of Parkinson's disease. - Canavan, A; Passingham, R; Marsden, C; Quinn, N; Wyke, M; Polkey, C (1989)
It is known that in animals learning is disrupted by caudate lesions; but there has been no agreement about whether pathology in the basal ganglia causes a similar impairment in man. Nineteen patients in the early stages of Parkinson's disease were tested on two associative learning tasks and on the Wisconsin Card Sorting Task; and their performance was compared with that of patients with frontal or temporal lobe lesions. On the two associative learning tasks there was no overall difference between the Parkinsonian group and the controls. However, a minority of the Parkinsonian patients performed very poorly on these tasks; and it was noted that these tended to be the older patients.